2021
DOI: 10.1088/1748-9326/abe5d5
|View full text |Cite
|
Sign up to set email alerts
|

Health impacts of fine particles under climate change mitigation, air quality control, and demographic change in India

Abstract: Despite low per capita emissions, with over a billion population, India is pivotal for climate change mitigation globally, ranking as the third largest emitter of greenhouse gases. We linked a previously published multidimensional population projection with emission projections from an integrated assessment model to quantify the localised (i.e. state-level) health benefits from reduced ambient fine particulate matter in India under global climate change mitigation scenarios in line with the Paris Agreement tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our results, taken together with the broader literature, indicate that targeted air pollution control policies would be needed in addition to ambitious climate action and improved socioeconomic development to address the public health burden of air pollution in India. 25 India has been identified as a global region with some of the largest health co-benefits of climate change mitigation due to air pollution and where savings from health co-benefits consistently outweigh mitigation costs. [26][27][28] Differences in scenarios and modeling assumptions make direct comparisons between our results and other studies challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, taken together with the broader literature, indicate that targeted air pollution control policies would be needed in addition to ambitious climate action and improved socioeconomic development to address the public health burden of air pollution in India. 25 India has been identified as a global region with some of the largest health co-benefits of climate change mitigation due to air pollution and where savings from health co-benefits consistently outweigh mitigation costs. [26][27][28] Differences in scenarios and modeling assumptions make direct comparisons between our results and other studies challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 75% of GHG emissions from the transportation sector are from road transport [ 43 , 44 ]. About 99.9% of the Indian population resides in areas exceeding the air quality permissible limits set by the World Health Organization (WHO) [ 45 , 46 ]. The air quality studies in India projected the PM 2.5 concentration to increase, resulting in premature mortality by 2050 even under the business-as-usual scenario [ 42 , 47 52 ].…”
Section: Problems With the Current Transportation Systemmentioning
confidence: 99%
“…Previous studies have shown that reductions in greenhouse gas emissions in line with climate change mitigation targets can bring substantial AAP improvements and health benefits in India, socalled co-benefits (West et al 2013, Silva et al 2016, Chowdhury et al 2018, Markandya et al 2018, Vandyck et al 2018, Sampedro et al 2020, and even more so when combined with stricter national measures for air quality control (Dimitrova et al 2021). However, scenario analysis from six different integrated assessment models (IAMs), which quantified the interactions between climate change mitigation and energy access, suggest that stringent climate policy might significantly slow down the transition to clean cooking fuels by affecting energy prices (McCollum et al 2018).…”
Section: Introductionmentioning
confidence: 99%